Identification of differentially expressed mRNAs and miRNAs in spermatozoa of bulls of varying fertility - Donnellan, Eimear M.; Perrier, Jean-Philippe; Keogh, Kate; Štiavnická, Miriam; Collins, Caitríona M.; Dunleavy, Elaine M.; Sellem, Eli; Bernecic, Naomi C.; Lonergan, Patrick; Kenny, David A.; Fair, Sean (Frontiers in Veterinary Science, 2022)
Bulls used in artificial insemination, with apparently normal semen quality, can vary significantly in their field fertility. This study aimed to characterize the transcriptome of spermatozoa from high (HF) and low (LF) fertility bulls at the mRNA and miRNA level in order to identify potential novel markers of fertility. Holstein-Friesian bulls were assigned to either the HF or LF group (n=10 per group) based on an adjusted national fertility index from a minimum of 500 inseminations. Total RNA was extracted from a pool of frozen-thawed spermatozoa from three different ejaculates per bull, following which mRNA-seq and miRNA-seq were performed. Six mRNAs and 13 miRNAs were found differentially expressed (P<0.05, FC>1.5) between HF and LF bulls. Of particular interest, the gene pathways targeted by the 13 differentially expressed miRNAs were related to embryonic development and gene expression regulation. Previous studies reported that disruptions to protamine 1 mRNA (PRM1) had deleterious consequences for sperm chromatin structure and fertilising ability. Notably, PRM1 exhibited a higher expression in spermatozoa from LF than HF bulls. In contrast, Western Blot analysis revealed a decrease in PRM1 protein abundance for spermatozoa from LF bulls; this was not associated with increased protamine deficiency (measured by the degree of chromatin compaction) or DNA fragmentation, as assessed by flow cytometry analyses. However, protamine deficiency was positively and moderately correlated with the percentage of spermatozoa with DNA fragmentation, irrespective of fertility group. This study has identified potential biomarkers that could be used for improving semen quality assessments of bull fertility.